Identifikasi Jenis Ikan Di Danau Teluk Petai, Desa Buluh Nipis, Kecamatan Siak Hulu, Kabupaten Kampar - Henri Siahaan; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTDuring the rainy season, the water as well as fish species from the Kampar River enter the Teluk Petai oxbow Lake. To find out the type of fish species present in the lake, a study was conducted from January to March 2019. Samplingswere carried out four times, once a week, usingnets (mesh size0,5 inch), fishtrap, and fishingline. The captured fish were then identified. Results shown that there were 171 fish sampled and they were belonged to 3 ordos, 8 families, and 15 species. They were Oxygaster anomarula, Puntius schwanefeldi, Rasbora cephalotaenia, Thynnichthys polylepis, Hampala macrolepidota, Anabas testudineus, Helostoma teminckii, Channa lucius, C. Striata, C. micropeltes, Oreochromis niloticus, Mystus nemurus, Clarias batrachus, Ompok hypopthalmus and Wallago leerii. The most common fish species are belonged to cyprinid. Keyword : Fish population, Channa species, Cyprinidae, Freshwater fish